THE PREVALENCE OF HYPODONTIA IN CHILDREN WITH CLEFT AND NONRELATED CONTROLS - Claudia COREGA; Alin SERBANESCU; Mihai COREGA; Mihaela BACIUT (Romanian Dental Association for Education, 2013)
The aim of this study was to compare the occurrence of hypodontia, dental age, and asymmetric dental development in children with cleft with a nonsibling control group. The study sample consisted of 30 children with cleft (aged 7.2 to 17.1 years) and 60 controls without cleft (aged between 7 and 18.8 years). Hypodontia, dental age, and asymmetric dental development were assessed on panoramic radiographs of the children with cleft and the control children without cleft. The cleft (p.001) group showed a significantly higher frequency of hypodontia and a significantly higher occurrence (cleft p.01) of asymmetric dental development, compared with the control group. Only a small, but insignificant delay in dental development could be found in the cleft group. The cleft subjects showed a significantly higher occurrence of hypodontia and asymmetric dental development than the non-cleft control group. This may suggest a genetic component for the occurrence of hypodontia and asymmetric dental development.